A 24/7 Public Possession: Understanding the Dissonance and Grace of Being a Post- Secondary Leader - Davison, Phil L. (Canadian Journal of Higher Education, 2012)
This study explores the perspectives and understandings of post-secondary leaders and their contexts as described through the qualitative experiences of 12 Maritime Canadian leaders (presidents and vice-presidents) who work in contemporary, publicly funded, post-secondary institutions. Four themes emerge: balancing daily dissonance, learning experientially to lead, creating learning spaces, and needing moments of grace. The research reveals that leaders seek deeper understandings of their work and their characterization.